The effect of special exercises using tools in teaching Arabic skills on the floor exercise mat in women's artistic gymnastics - Shehab, Asst.L.. Ragda Ahmed; Akbar, Asst.L. Roaa Akram; Mohsen, Asst.L. Ali Saadi; Hamza, Asst.Prof.Dr. Jamal Sakran (Sulaimani Journal for Humanities, 2026)
Artistic gymnastics, in both its men's and women's divisions, is characterized by the need for fluidity and great precision in executing its motor skills. The aim of this research is to determine the effect of specific exercises using equipment on teaching the Arabic technique on the floor exercise mat in women's artistic gymnastics. The research hypothesis is that there are statistically significant differences in the performance level of the Arabic technique between the pre-test and post-test for the experimental group, favoring the post-test. The researchers used the experimental method (a single-group pre-test/post-test design) as it is suitable for the nature of the problem being solved. The research population consisted of (5) female gymnasts from the Workers' Club in Baghdad, aged (6-8) years, who train at the Al-Nusour College hall in Baghdad's Al-Karkh district. The researchers used two gymnasts from the Al-Amana Sports Club for a pilot study, and the sample settled on five gymnasts for the main study, representing (75%). The two gymnasts for the pilot study represented (25%). The researchers concluded: 1- The use of equipment-specific exercises contributed to the development of Arabic language skills on the floor exercise machine. 2- The equipment provided a variety of exercises that contributed to learning the skill. The researchers recommended: 1- The necessity of diversifying the use of equipment for each skill, using exercises appropriate to its design. 2- Using the equipment and exercises, along with adding other exercises on the vaulting platform, to learn the same skill.
Keywords: Gymnastics; round off; Special exercises